Benzimidazole-modified polyaniline micro-shells for electrochemical detection of cadmium in aqueous solution - Eldhose V. Varghese; Bejoy Thomas; Carsten Schwandt; Praveen C. Ramamurthy; Alex Joseph (Journal of Electrochemical Science and Engineering, 2023)
Benzimidazole-functionalized polyaniline (BMPANI) was synthesized by interfacial polymerization technique and used for electrochemical sensing of cadmium ions in an aqueous solution. The material was characterized for its structural and morphological features using Fourier-transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), and scanning electron microscopy (SEM). The BMPANI has a micro-shell structure produced from the self-assembly of the monomer units in solution before the polymerization reaction. The material was trialed for cadmium ion sensing using a BMPANI-modified carbon paste electrode (BMPANI-CPE). Electrochemical techniques, i.e., cyclic voltammetry (CV) and differential pulse anodic stripping voltammetry (DPASV), were performed to assess the sensing characteristics of the material. Various electrode preparation parameters, i.e., deposition potential, pH of deposition solution, and thickness of the active layer, were optimized to achieve the highest level of sensitivity. The selectivity towards cadmium ions, interference from other ions, as well as stability and reusability of the BMPANI-CPE, were also examined and found to be satisfactory.